Earnings per Share Forecasting: Accuracy of Random Walk and Random Walk with Drift Models - Klayme, Abdallah Joseph (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The research aims to compare the forecasting power for earning per share (EPS) using two models, namely the random walk model and the random walk with drift model. The study uses historical EPS data of three companies listed in the Standard and Poor’s 500. The three companies are selected based on their ascending beta values from de fensive, neutral, and aggressive stock categories. The ascending beta values for these three companies, namely NextEra, Oracle, and FedEx, are 0.16, 1.0 and 1.3. The three companies have EPS data for 30 years between 1990 and 2019. For the respective defensive and neutral stocks of NextEra (Beta = 0.16) and Oracle (Beta = 1.0) compa nies, the results show that the random walk model has better forecasting power meas ured by both the mean absolute error (MAE) and the mean square error (MSE) fore casting accuracy dispersion measures, but with higher positive bias measure of the average error (AVE). For the aggressive stock of FedEx company (Beta = 1.3), con flicting results are found where the random walk with a drift model performs better in terms of MAE dispersion measure and the random walk model performs better in terms of MSE dispersion measure. In terms of AVE bias measure, the random walk model has a slight positive bias whereas the random walk with a drift model has a high neg ative bias. Additionally, the forecasting power for EPS gets worse as the beta of stock increases for the case of these three companies. Keywords: forecasting, earnings per share, beta, accuracy

ÖZ: Bu araştırmanın amacı rastgele yürüyüş modeli ve rastgele yürüyüş sapma modeli olmak üzere iki model kullanarak hisse başına kazanç (HBK) için tahmini gücü karşılaştırmaktır. Bu çalışmada, Standard ve Poor’s 500 listesinde yer alan üç şirketin verisi kullanılmıştır. Üç şirket, savunmacı, tarafısız ve agresif hisse senedi kate gorilerinden artan beta değerlerine göre seçilmiştir. NextEra, Oracle ve FedEx isimli üç şirket için artan beta değerleri 0.16, 1.0, ve 1.3’tür. Üç şirketin, 1990 ve 2019 yılları arasında 30 yıllık verisi bulunmaktadır. Araştırmanın sonucu, NextEra (Beta= 0.16) ve Oracle (Beta= 1.0) sirketlerinin, ilgili savunma ve tarafsız hisse senetleri için rastgele yürüyüş modelinin hem ortalama mutlak hata (MAE) hem de ortalama kare hata (MSE) tahmin doğruluğu dağılım ölçüleri ile ölçülenlerin daha olumlu tahmin gücüne sahip olduğunu, ancak ortalama hatanın (AVE) daha yüksek bir olumlu önyargı ölçümü olduğu görülmüştür. FedEx (Beta= 1.3) şirketinin agresif hisse senedi için retgele yürüyüş sapma modelinin ortalama mutlak hata açısından daha iyi performans sergilediği ve rastgele yürüyüş modelinin ortalama kare hatası dağılım ölçü açısından daha iyi performans gösterdiği gibi çelişkili sonuçları olduğu saptanmıştır. Ortalama hata önyargı ölçüsü açısından, rastgele yürüyüş modeli hafif olumlu sapmaya sahip ken, rastgele yürüyüş sapma modelinin yüksek olumsuz önyargıya sahip olduğu görül müştür. Ayrıca, bu üç şirketin durumu için hisse senedinin betası arttıkça, HBK için tahmin gücünün daha da kötüleştiği belirlenmiştir. Anahtar kelimeler: hisse başına kazanç tahmini, beta, kesinlik
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Cahit Adaoğlu.
Keywords: Banking and Finance; Economic forecasting; forecasting; earnings per share; beta; accuracy